PENERAPAN E-GOVERNMENT DI BIDANG PELAYANAN PUBLIK PADA BIDANG PELAYANAN HUKUM KANWIL KEMENKUMHAM SULUT - Waloni, Patrick Fanny; Bida, Obed; Zubaidah, Ida (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to evaluate the implementation of E-Government in an effort to improve the quality of public services at the Regional Office of the Ministry of Law and Human Rights in North Sulawesi Province. Based on the literature review, E-Government has the potential to encourage efficiency in administration, expand access to public services, and increase transparency and accountability in governance. The success of E-Government implementation is influenced by the readiness of information technology infrastructure, commitment from the government, active community participation, and strengthening human resource capacity. The research findings show that although the implementation of E-Government has a positive impact, there are still a number of obstacles that need to be overcome, such as lack of regulatory support, budget constraints, the need for technological infrastructure development, low digital literacy of the community, and lack of ongoing training for state apparatus. Therefore, this study recommends the need for increased investment in terms of supporting regulations, budget allocation, development of information technology infrastructure, community education, and ongoing training for employees. In addition, it is also recommended to recruit employees who are in accordance with their field of competence, carry out periodic public service evaluations, and strengthen cooperation between local governments, academics, and community communities in North Sulawesi. The implementation of these recommendations is expected to increase the effectiveness of E-Government and provide a greater contribution to the quality of public services in the region